Head motion in children with ADHD during resting-state brain imaging - Kong,Xiang-zhen (PeerJ PrePrints, 2014)
Resting-state functional MRI (rs-fMRI) has become an important method for analyzing the neural mechanisms underlying mental disorders. But studies targeting head motion during an rs-fMRI examination are rare. Since head motion may pollute the data in the neural imaging studies and further mislead the understanding of the causes of some disorders, systematic investigations on this topic were badly needed. To this end, in this study, children with attention-deficit/hyperactivity disorder (ADHD) and demographically-matched typically developing control (TDC) participants underwent an rs-fMRI examination. We obtained a summary motion index and six mean single head motion parameters (three translational and three rotational) for each participant. With the summary index, we found that motion was significantly increased in the ADHD group and the results showed that the increase was mainly contributed by the motion around and along the superior-to-inferior direction. Moreover, the classification analysis showed that these head motion parameters during scanning could accurately distinguish children with ADHD from the healthy control group. These results suggest that accounting for head motion during scanning may be helpful for ADHD diagnosis and treatment with neuroimaging.
Keywords: Head motion; ADHD; resting-state fMRI